Peran Balai Pemasyarakatan Kelas II Polewali dalam Pembinaan Recidives Tindak Pidana Pencurian oleh Anak - latif, Abdul Latif; zulfa, Zulfawati; jalil, Jalil B (JISH: Jurnal Ilmu Syariah dan Hukum, 2025)
The problems studied in this study are: (1) What is the role of BAPAS Class II Polewali against Recidives for the crime of child theft, (2) What are the obstacles faced by BAPAS Class II Polewali in fostering Recidives for criminal acts of theft by children. The objectives to be achieved in this study are: (1) To find out the role of BAPAS Class II Polewali against Recidives for the crime of child theft, (2) To find out what are the obstacles faced by BAPAS Class II Polewali in fostering Recidives for the crime of theft by children.The research conducted is legal research that is descriptive analysis and uses a type of sociological juridical research. Through descriptive research, researchers try to describe events and events that are the center of attention without giving special treatment to these events. This study uses primary data and secondary data by processing data from primary legal materials, secondary legal materials and tertiary legal materials. The research conducted is legal research which is descriptive analysis in nature and uses normative and empirical research types. Through descriptive research, researchers try to describe events and events that are the center of attention without giving special treatment to these events. This study uses primary data and secondary data by processing data from primary legal materials, secondary legal materials and tertiary legal materials. From the research results obtained, Bapas is obliged to provide assistance to children who commit criminal acts in accordance with Law Number 11 of 2012 concerning the Child Criminal Complaint System, as well as the role of PK Bapas in this case is very important because if the trial continues without PK from Bapas then the trial will be legally void. Obstacles experienced by Bapas in carrying out Recidives Guidance on the Crime of Theft by Children, namely that sometimes the parents of the victims are stubborn, and the parents of the perpetrators are indifferent to the child so that the child commits the same crime. And another obstacle is the absence of Griya Abhipraya (Safe House for Children) to place children.